Legal Regulation of Hybrid Work Models and Their Impact on Work-Life Balance: A Case Study of Ukraine - Hryn Dmytro V.; Yaroshenko Oleg M.; Tykhonovych Oleksii Y.; Hryhorenko Dmytro A.; Pavlichenko Volodymir (Comparative Southeast European Studies)
The pandemic and Russia’s full-scale invasion of Ukraine have resulted in adjustments to the organisation of working hours in various areas of society, and not only in Ukraine. Employees look for remote work opportunities, while employers strive to control employees’ work by increasingly offering hybrid work models in addition to traditional work formats. Such hybrid work models comprise a combination of remote work and work at the employer’s premises. However, the authors argue that the legal regulation of this work format should be reconsidered in terms of its impact on work-life balance. Hybrid work formats should still provide an employee with the ability to separate work and personal life in order to avoid burnout and to genuinely be more effective. The purpose of this article is to analyse the legal regulation of “non-traditional” forms of labour organisation and develop recommendations for further improvement.